2017
DOI: 10.5539/ells.v7n3p28
|View full text |Cite
|
Sign up to set email alerts
|

Level of Reflective Practice amongst Saudi Female Postgraduate Students at KSU

Abstract: This paper investigates the level of reflective practice amongst Saudi female postgraduate students at King Saud University. The study is quantitative in nature, whereby a reflective practice self-assessment scale was administered to assess the reflective practice of 201 female postgraduate students at KSU. The scale concentrates on five dimensions; the ability and freedom to reflect, questioning assumptions, considering others' viewpoints, using reflective methods/tools, and frequency of the refection on even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…This could be due to the fact that females tend to have a positive attitude toward their profession, do not avoid taking responsibility, and act sincerely. [20] This finding disagreed with our results along with the other similar studies by Lew and Schmidt[5] and Tricio et al [2] in which no significant gender differences were observed.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be due to the fact that females tend to have a positive attitude toward their profession, do not avoid taking responsibility, and act sincerely. [20] This finding disagreed with our results along with the other similar studies by Lew and Schmidt[5] and Tricio et al [2] in which no significant gender differences were observed.…”
Section: Discussioncontrasting
confidence: 99%
“…A study carried out by Omar et al (2017) on Saudi female students at the King Saud University showed that the reflective learning model helped building the students' critical thinking and curiosity for new knowledge and insights. It also developed high-level skills and helped students to connect new knowledge with the previously gained knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, she proposed that it is essential to provide in-service teachers with professional training on reflective teaching, and cooperation with college administrators to establish an inquiry culture among teacher-learners. Omar et al (2017) administered a reflective practice self-assessment scale in order to evaluate the reflective practice of 201 female postgraduate students at King Saud University. The scale focused on five aspects: being able reflect, questioning assumptions, taking into consideration others' points of view, using reflective methods, and the frequency of the reflective practice events.…”
Section: Definition Of Reflectionmentioning
confidence: 99%